Preliminary findings from the Delirium and Population Health Informatics Cohort (DELPHIC) – Qatar Study - Al Hamad, Hanadi; Chandran, Mani; Manikoth, Pravija Talapan; Davis, Daniel; Sathian, Brijesh (Nepal Journal of Epidemiology, 2024)
The DELPHIC-Qatar cohort study enrolled a total of 638 participants aged 70 years and above, with 277 males and 361 females from 10th March 2021 to 30th June 2024. The sex-wise distribution of risk and outcomes revealed significant findings. Among the participants, 47.8% were classified as high risk, with a higher proportion of females (50.7%) than males (44.0%). Conversely, 34.6% of the cohort was categorized as low-risk, with 36.5% of men and 33.2% of women. Delirium was observed in 17.6% of the total cohort, with a slightly higher incidence in males (19.5%) than in females (16.1%). Mortality rates were comparable between the sexes, with 23.8% in males and 23.0% in females, resulting in an overall mortality rate of 23.4% in the cohort.